2021
DOI: 10.1088/1361-6560/abd955
|View full text |Cite
|
Sign up to set email alerts
|

Stereoscopic portable hybrid gamma imaging for source depth estimation

Abstract: Advances in gamma imaging technology mean that is now technologically feasible to conduct stereoscopic gamma imaging in a hand-held unit. This paper derives an analytical model for stereoscopic pinhole imaging which can be used to predict performance for a wide range of camera configurations. Investigation of this concept through Monte Carlo and benchtop studies, for an example configuration, shows camera-source distance measurements with a mean deviation between calculated and actual distances of <5 mm for im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…The maximum distance error of 5 mm at a 5-cm source depth appears promising. Bugby et al demonstrated the use of a portable gamma-camera equipped with a pinhole collimator to estimate the source depth based on stereoscopic imaging [ 30 ]. Acquisition of images from different angles could be applied also for the camera used herein, which could possibly give improved accuracy in position estimates from our multi-photopeak method.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum distance error of 5 mm at a 5-cm source depth appears promising. Bugby et al demonstrated the use of a portable gamma-camera equipped with a pinhole collimator to estimate the source depth based on stereoscopic imaging [ 30 ]. Acquisition of images from different angles could be applied also for the camera used herein, which could possibly give improved accuracy in position estimates from our multi-photopeak method.…”
Section: Discussionmentioning
confidence: 99%
“…The Sentinella 102 places an optical module beside the gamma-imaging module, with images aligned through a calibration process [58]. Stereoscopic imaging, which provides distance information, has also been explored for the Sentinella 102 (optical only) and the HCGC (gamma-optical, including source depth estimation) [58,79]. Example gamma-optical multimodality images are shown in Figure 5.…”
Section: Trends In System Functionalitymentioning
confidence: 99%
“…SLNB has been identified as a suitable clinical application for coded-aperture collimators [93]. A further benefit of codedaperture collimation is that the longitudinal depth of sources within an image can be estimated, as each superimposed projection that makes up the total image is acquired at a different sampling position [9,94], similar to stereoscopic imaging with conventional collimator geometries without the need for multiple images [79]. The addition of sourcedepth information to IGCs provided by coded-aperture collimators is notably valuable for intraoperative radioguidance due to the complexity of many surgical fields.…”
Section: Alternative Collimator Geometriesmentioning
confidence: 99%
“…The advancements have initiated comprehensive investigations of the DI concept in DL techniques. The most critical challenge towards the application of DL is the absence of datasets that fit the problem [ 110 , 111 , 112 ]. This challenge may also be of great importance for the MDE network.…”
Section: Mde Applying Deep Learning Training Mannersmentioning
confidence: 99%